A cross-sectional study to assess the knowledge, attitude and practice about COVID-19 following the 2nd wave among the residents of Mysuru city - Akbar, Shabeena; Vadaga, Vijaylakshmi Rao; Anil, Deepak; Murthy, M. R. Narayana; Kumar D., Sunil (International Journal Of Community Medicine And Public Health, 2023)
Background: COVID-19 is an infectious disease which emerged at the end of 2019 in China and soon took over the world. Interventional measures such as lockdown and health education were provided to contain the spread of the infection. The present study was conducted to assess the knowledge, attitude and practice of the people of Mysuru and clarify any misconceptions regarding the disease or COVID-19 vaccination following the 2nd wave of the disease. Methods: A cross-sectional study was conducted from June to July 2021 to assess the knowledge, attitude and practice about the 2nd wave of COVID-19 among the people residing in Mysuru city. The aim was to correct any misconceptions about COVID-19 vaccination, black fungus and basic practices to combat the ongoing COVID-19 pandemic. A sample size of 142 was interviewed with a questionnaire through a door-to-door survey. Results: Though awareness about black fungus and basic etiquette was present among the people, there was poor knowledge about the benefits and use of COVID-19 vaccination among the people. Conclusions: Providing health education is essential to provide knowledge to the public. However, clarifying their doubts and queries is also an essential component to ensure better attitude and widespread practice of the containment measures.